2019
DOI: 10.1186/s40814-019-0395-8
|View full text |Cite
|
Sign up to set email alerts
|

Combining Wireless Technology and Behavioral Economics to Engage Patients (WiBEEP) with cardiometabolic disease: a pilot study

Abstract: BackgroundThe long-term management of cardiometabolic diseases, such as type 2 diabetes and hypertension, is complex and can be facilitated by supporting patient-directed behavioral changes. The concurrent application of wireless technology and personalized text messages (PTMs) based on behavioral economics in managing cardiometabolic diseases, although promising, has not been studied. The aim of this pilot study was to evaluate the feasibility and acceptability of the concurrent application of wireless home b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Another study 19 evaluated the feasibility and acceptability of the simultaneous application of wireless home blood pressure monitoring (as an example of "nudging") and approaches targeting pharmacological treatment and lifestyle habits in patients with cardiometabolic disease (type 2 diabetes and/or hypertension). The patients with cardiometabolic disease studied reported that lifestyle-targeting text messaging approaches were feasible and acceptable, and that the text messages were easy to understand (88%) and were sent at an Connected Health Interventions to Cardiovascular Disease Prevention Agher et al 549 appropriate frequency (71%), in appropriate language (88%).…”
Section: Connected Health Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study 19 evaluated the feasibility and acceptability of the simultaneous application of wireless home blood pressure monitoring (as an example of "nudging") and approaches targeting pharmacological treatment and lifestyle habits in patients with cardiometabolic disease (type 2 diabetes and/or hypertension). The patients with cardiometabolic disease studied reported that lifestyle-targeting text messaging approaches were feasible and acceptable, and that the text messages were easy to understand (88%) and were sent at an Connected Health Interventions to Cardiovascular Disease Prevention Agher et al 549 appropriate frequency (71%), in appropriate language (88%).…”
Section: Connected Health Interventionmentioning
confidence: 99%
“…The patients with cardiometabolic disease studied reported that lifestyle-targeting text messaging approaches were feasible and acceptable, and that the text messages were easy to understand (88%) and were sent at an Connected Health Interventions to Cardiovascular Disease Prevention Agher et al 549 appropriate frequency (71%), in appropriate language (88%). Most of the studies used "smartphone health applications (connect)" [8][9][10][11][12]15,16,19,20,22,[24][25][26][27] . "Focus group" (do) and "Education" (read) were used together in two articles.…”
Section: Connected Health Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pilot study tested the effects of a combined intervention on 12 patients with type 2 diabetes and/or hypertension. 75 Patients were provided with wireless home blood pressure (BP) monitors and motivational text messages and advice for seven weeks. Mean blood pressure, medication adherence, and satisfaction with the program all increased at the end of the study.…”
Section: Personalized Lifestyle Text Messagesmentioning
confidence: 99%
“…Alternatively, mobile health technologies (mHealth) are health-related applications on mobile phones or other “smart devices” (e.g., apps, specialty websites, or smartwatches) and can include appointment and medication reminders through text messages. 7 Health care professionals may choose to implement a combination of telehealth strategies to manage CVD and its risk factors and supplement services through text messaging (e.g., medication reminders or lifestyle coaching), 8 synchronous teleconferencing or videoconferencing with pharmacists and other health care professionals, 9–16 and interactive voice response (IVR) systems. 17…”
Section: Introductionmentioning
confidence: 99%